PUSH NOTIFICATION MONITORING SISTEM PINTU AIR BERBASIS ANDROID MENGGUNAKAN FIREBASE CLOUD MESSAGING - Frandia Fernando; Arini Arini; Feri Fahrianto (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
Flood disaster is very common, especially in Jakarta City. One way to control water debit is to create a dam or reservoir. In each reservoir there is a water gate which serves to dispose of unwanted water gradually or continuously according to the water volume present in the dam. The Regional Disaster Management Agency (BPBD) Jakarta City needed a system that can monitor any existing water gates of the reservoir, this is to facilitate water gate inspectors to provide information. By using firebase cloud messaging technology that will be applied in the application of push-based android water doors. The application will provide notification and water gate data in real time, making it easier for users to get data in real time. Firebase Cloud Messaging is a cross platform solution that allows you to send messages reliably at no cost. In addition, the use of API as a processing medium to pull data from the web BPBD, optimize its function to mobile android. BPBD as the agency that tackling the disaster can know the state of the environment quickly and accurately. Applications created not only made for BPBD only but the general public can also to know the condition of the water gate. In addition, there are also ways of handling floods and what to do at each level of water level.For the next, this application can add other technollgy also IoT technology.